Diabetic Ketoacidosis in A Person with Insulin Pump-Treated Type 1 Diabetes Mellitus while Following A Very Low Carbohydrate Diet – A Case Report - Tikander, Emil; Ranjan, Ajenthen; Schmidt, Signe; Nørgaard, Kirsten (Archives of Clinical and Medical Case Reports, 2019)
This report describes a male with insulin pump-treated type 1 diabetes mellitus admitted with diabetic ketoacidosis after a gastroenteritis while following a very low carbohydrate diet. Combining such diet, using an insulin pump and suffering a gastroenteritis may represent an increased risk of diabetic ketoacidose.